Emerging Trends in Overcoming the Weather Barrier to Sustainable Mobility in Gulf and Tropical Cities. Issue 1 (1st May 2022) - Al-Atroush, M.E.; Mustaffa, Z.; Sebeay, T.A.
Abstract: Several studies predicted that in case of the continuous rising concentrations of anthropogenic greenhouse gases (GHGs), the gulf region might experience intolerable temperatures to humans. Such terrible weather may have a severe consequence on different vital activities in different Gulf countries, such as the Muslim rites of Hajj in Mecca city. However, supporting the global mitigation efforts would significantly minimize the seriousness of the expected impacts. With that in mind, hot weather was reported as the significant barrier to sustainable mobility in those countries. Their current mobility is heavily dependent on privately-owned fossil-fueled vehicles rather than other sustainable transport choices. This paper reviewed the most recent innovative and solutions to overcome the problems associated with the hot climate. The review focused on the new techniques concerned with reducing the pavement surface temperature and the corresponding decreases in the ambient air temperature, aiming to promote sustainable mobility modes in hot climate cities. The paper also identified future research needs to fulfill each proposed solution's scientific and practical gap and overcome the weather barrier.